Porte sculptée au Village du Kinh-Luoc - Auteur inconnu (Wikimedia Commons, 1945)
Notice image issue de Wikimedia Commons. Titre: Porte sculptée au Village du Kinh-Luoc. A postcard depicting the tomb of the Nguyn Dynasty Mandarin (and the Viceroy of Tonkin) Hoàng Cao Khi in the city of Hanoi, in the French protectorate of Tonkin.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; Carte postale